Konsep dan Peran Pendidikan untuk Meningkatkan Literasi dalam Perspektif Islam - Mubarok, Ahta Abdul Mursyid Husni; Aziz, Muhammad Abdul (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2023)
This research looks at how education helps people learn to read and write from an Islamic perspective. The ability to read and write are literacy activities necessary for learning. The purpose of this study is to show how the role of education in Islam improves literacy skills by describing educational principles and educational institutions. This research brings important insights into acquiring literacy skills, which are most emphasized in Islamic education from the first revelation of the Qur'an. The focus of discussion is on the concept of literacy and how the principles of education in Islam and the institutionalization of education in Islam improve literacy skills. As for this research, the method of analysis and historical description was used during the research. The results of this study found that literacy opens the door to acquiring knowledge and is essential for the development of any country. In addition, Islam views education as an obligation that must be fulfilled to ensure and promote literacy in worldly and heavenly education. According to the history of Islamic education, that educational institutions can successfully improve literacy levels.Keyword: Role of Education; Literacy Improvement; Islamic Perspective.